Prevalence of endometriosis and adenomyosis at transvaginal ultrasound examination in symptomatic women - Sofie Orlov; Ligita Jokubkiene (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Prevalence of endometriosis is commonly reported based on surgery findings and varies widely depending on study population and indication for surgery. Symptoms such as dysmenorrhea, pelvic pain, dyspareunia, dysuria, and dyschezia can be associated with endometriosis and adenomyosis. Transvaginal ultrasound examination is proposed to be the first‐line diagnostic method, nevertheless there are no published ultrasound‐based studies reporting prevalence of endometriosis and adenomyosis in symptomatic women other than those scheduled for surgery. The aim of this study was to determine the prevalence of endometriosis and adenomyosis as assessed by transvaginal ultrasound in women with symptoms suggestive of endometriosis and adenomyosis. Material and methods This is a retrospective cross‐sectional study performed at a tertiary‐care center including 373 symptomatic women who were systematically examined with transvaginal ultrasound by an experienced ultrasound examiner. Before ultrasound examination women filled in a questionnaire including self‐assessment of the severity of their symptoms (dysmenorrhea, chronic pelvic pain, dyspareunia, dysuria, dyschezia) using a visual analog scale. Abnormal findings in the uterus, ovaries, bowel, urinary bladder, uterosacral ligaments, and rectovaginal septum were noted, and their size and location were described. Prevalence of endometriosis, adenomyosis, endometrioma, and deep endometriosis in different anatomical locations was reported. Results Prevalence of ovarian endometrioma and/or deep endometriosis was 25% and of adenomyosis was 12%. Prevalence of endometrioma was 20% and of deep endometriosis was 9%, for each location being 8% in the bowel, 3% in the uterosacral ligaments, 3% in the rectovaginal septum and 0.5% in the urinary bladder. Conclusions In symptomatic women examined with transvaginal ultrasound by an experienced ultrasound examiner, ovarian endometrioma and/or deep endometriosis was found in one of four women and adenomyosis in one of nine women. Deep endometriosis was present in one of 11 women. Despite having symptoms, half of the women had no abnormal ultrasound findings.